2007
DOI: 10.1038/sj.jhh.1002259
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-ankle vs carotid-femoral pulse wave velocity as a determinant of cardiovascular structure and function

Abstract: Carotid-femoral pulse wave velocity (cf-PWV) is a validated marker of arterial stiffening over the central arteries. Brachial-ankle pulse wave velocity (ba-PWV) integrates the mechanical properties from both the central and peripheral arteries and may be more representative than cf-PWV as arterial load for left ventricle (LV). We compared ba-PWV with cf-PWV for the association of cardiovascular structure and function in 320 subjects with various degrees of abnormality in cardiac structure and function. ba-PWV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
116
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 36 publications
5
116
0
6
Order By: Relevance
“…Indeed, baPWV has been reported to be a better marker of cardiac load than carotid-femoral PWV. 32 Previous studies have demonstrated that baPWV predicts cardiovascular events in individuals at high risk, including those with acute coronary syndrome, 33 the elderly, 34 those on hemodialysis 35 and those with coronary artery disease. 36 We have further extended the clinical significance of baPWV by showing that this index provides important information for the screening of low-to-moderate risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, baPWV has been reported to be a better marker of cardiac load than carotid-femoral PWV. 32 Previous studies have demonstrated that baPWV predicts cardiovascular events in individuals at high risk, including those with acute coronary syndrome, 33 the elderly, 34 those on hemodialysis 35 and those with coronary artery disease. 36 We have further extended the clinical significance of baPWV by showing that this index provides important information for the screening of low-to-moderate risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used baPWV, the surrogate marker of aortic PWV to evaluate the large artery elasticity, because baPWV has been proved closely related to aortic PWV and has been used as a well-accepted surrogate end point predicting cardiovascular events in earlier studies. 16,17,38 However, large sample and prospective studies will still be needed to further confirm its usefulness in clinical practice. Further investigation is now being performed in our laboratory to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…15 baPWV has been testified to be the alternative of aortic PWV and shown to be a better marker for the clinical evaluation of vascular abnormality. 16,17 Circulating EMPs emerged as the sensitive marker of endothelial perturbation in response to adverse stimuli. 18 It has been reported that in patients with hypertension, increased EMPs and reduced artery elasticity are present.…”
Section: Introductionmentioning
confidence: 99%
“…be more representative than cfPWV of arterial load. [31][32][33][34] One published validation study of baPWV demonstrated both validity and reproducibility of baPWV when compared with aortic PWV. 35 The utility of baPWV versus cfPWV in stroke risk assessment is worth mentioning.…”
Section: Discussionmentioning
confidence: 99%